An Exploration of Jonathan Swift's Use of Satire in Portraying The Problems of The Poor in Ireland in a Modest Proposal. - Kazigye, Doreen (Kabale University, 2024)
The purpose of this study was to explore how Jonathan Swift uses satire in portraying the problems of the poor in Ireland.